6,12-Dihydrodipyrido[1,2-a:1′,2′-d]pyrazinium bis(perchlorate) - Kim, Nam-Ho (International Union of Crystallography, 2009)
In the title compound, C(12)H(12)N(2) (2+)·2ClO(4) (−), the dihedral angle between the two outer pyridine rings of the dication is 44.8 (1)°. In the crystal, weak intermolecular C—H⋯O hydrogen bonds occur.